2013
DOI: 10.1371/journal.pone.0077227
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Celecoxib and Bupropion in a Model of Chronic Inflammation-Related Depression in Mice

Abstract: This study was aimed to characterize the depression-like behaviour in the classical model of chronic inflammation induced by Complete Freund’s Adjuvant (CFA). Male Swiss mice received an intraplantar (i.pl.) injection of CFA (50 µl/paw) or vehicle. Behavioural and inflammatory responses were measured at different time-points (1 to 4 weeks), and different pharmacological tools were tested. The brain levels of IL-1β and BDNF, or COX-2 expression were also determined. CFA elicited a time-dependent edema formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 69 publications
(90 reference statements)
3
60
1
4
Order By: Relevance
“…[1][2][3][4] If this is true, then anti-inflammatory drugs may improve depression outcomes by attenuating the neuroinflammatory changes 5 or by other mechanisms, such as increased norepinephrine and serotonin levels. 6 Data from animal models show that NSAIDs in monotherapy 7,8 and in combination with conventional antidepressants 5 indeed attenuate indices of inflammation and depression. What do the clinical data show?…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] If this is true, then anti-inflammatory drugs may improve depression outcomes by attenuating the neuroinflammatory changes 5 or by other mechanisms, such as increased norepinephrine and serotonin levels. 6 Data from animal models show that NSAIDs in monotherapy 7,8 and in combination with conventional antidepressants 5 indeed attenuate indices of inflammation and depression. What do the clinical data show?…”
Section: Introductionmentioning
confidence: 99%
“…Tramadol and some opioid agonists have been declared to improve depressive symptoms [22,23]. Celecoxib and piroxicam have been shown to display antidepressant effect in human and animal studies [8,[24][25][26]. Acute administration of paracetamol has been shown to cause antidepressant-like effects and display synergistic effect with fluoxetine in FST and tail suspension tests without affect locomotor activity [27].…”
Section: Discussionmentioning
confidence: 99%
“…Dipyrone has been shown to produce anticonvulsant effect in rats exposed to the audiogenic and electroshock-induced seizures [7]. Dipyrone was also found to reverse the mechanical allodynia induced by CFA, and reduce the immobility time in tail suspension test in a study that compares the depression-like behavior of analgesics and bupropion in a model of chronic inflammation-related depression in mice [8].…”
mentioning
confidence: 97%
“…Previous studies have shown that bupropion can reduce the inflammatory response [9], and animal intestinal I/R models have demonstrated a decrease in TNF-α [10]. To our knowledge there are no studies that evaluate the effect of bupropion as a pharmacologic preconditioner in renal I/R.…”
Section: Introductionmentioning
confidence: 98%